SOCIO-ECONOMIC ANALYSIS OF THE PRODUCTION OF GAS PROCESSING INDUSTRY ENTERPRISES (Conference Zone, 2021)
in this article, the socio-economic analysis of its activities on “Shurtan GCC” LLC is presented and the analysis is based on a clear table. The volume of products produced by the enterprise and its several projects are mentioned. The directions of development of the enterprise are explained in detail.